Financial literacy and entrepreneurial motivation: An empirical analysis of the mediating role of financial behaviour - Deny Ismanto; Zhou Wanbing (Universitas Ahmad Dahlan, 2025)
Purpose-This study aims to analyze the role of financial literacy in increasing student entrepreneurial motivation by considering financial behavior as a mediating variable. By building on previous studies on the importance of financial capacity in entrepreneurial decision-making, this study fills the gap regarding how financial literacy and behavior interact in influencing entrepreneurial motivation in the context of students in Yogyakarta, Indonesia. Methodology-This study used purposive sampling with 163 student respondents in Yogyakarta, Indonesia. The questionnaire was distributed online and filled out independently by the students. The data was then processed using SmartPLS 4.0, with validity and reliability tests, as well as hypothesis testing to assess the relationship between variables based on the respondents' answers. Findings-The results show that all hypotheses were accepted. Financial literacy has a positive and significant effect on financial behavior and entrepreneurial motivation. Financial behavior also has a positive and significant effect on entrepreneurial motivation. In addition, financial behavior was found to significantly mediate the relationship between financial literacy and entrepreneurial motivation, confirming the theoretical framework of the Theory of Planned Behavior. Research Limitations-This study is limited to students in Yogyakarta, Indonesia, and uses purposive sampling with self-reported data. The research model only covers financial literacy, financial behavior, and entrepreneurial motivation, without considering other variables such as self-efficacy, social support, or other factors that may influence entrepreneurial motivation. Novelty-This study makes a theoretical contribution by integrating financial literacy and financial behavior into a TPB-based entrepreneurial motivation model. Practically, this study confirms that financial education not only increases knowledge but also shapes financial behavior, which is the foundation of entrepreneurial motivation. These findings open up opportunities for further research testing other contextual factors such as family support, self-efficacy, and early business experience.